1982
DOI: 10.1346/ccmn.1982.0300408
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for Benzidine-Vermiculite

Abstract: A combination of X-ray diffraction, infrared, and chemical data has established that the ion exchange of vermiculite with singly charged benzidine cations in an aqueous solution at pH 1.6 results in a black, highly ordered benzidine-vermiculite intercalate. The intercalate has a basal spacing of 19.25/~ and a primitive unit cell with "a" and "b" edges parallel and equal to those of vermiculite. The number of benzidine molecules per cell is equal to its electric charge. In this structure the benzidine molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…The present study, based upon three-dimensional data, has located the ring planes to be about _+ 60 ~ to [010]. In the vermiculite-anilinium intercalate (Figure 4) the planes of the aromatic rings are therefore similarly oriented to those proposed by Slade and Raupach (1982) for a vermiculite-benzidine intercalate.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The present study, based upon three-dimensional data, has located the ring planes to be about _+ 60 ~ to [010]. In the vermiculite-anilinium intercalate (Figure 4) the planes of the aromatic rings are therefore similarly oriented to those proposed by Slade and Raupach (1982) for a vermiculite-benzidine intercalate.…”
Section: Discussionsupporting
confidence: 65%
“…A similar close-packed arrangement exists in aniline hydrochloride (Brown, 1949) and in aniline hydrobromide (Nitta et al, 1948) and has been postulated for benzidine in a vermiculite-benzidine intercalate (Slade and Raupach, 1982). For the arrangement shown in Figure 5, the repeat distance along a row perpendicular to the b-axis is ~ 5.33/~.…”
Section: Superstructuresupporting
confidence: 72%
See 1 more Smart Citation
“…The molecules were probably aligned nearly "vertically" on the surface, thereby permitting overlap between a--orbitals of the electron donor (diamine) and acceptor (diimine) as shown in Figure 6b. A similar complex between benzidine and vermiculite at high adsorption levels has been described (Slade and Raupach, 1982). The charge-transfer complex was oxidized to the same degree as the radical monomer, and involved an association of the 2-electron oxidation product (diimine) and the unoxidized diamine.…”
Section: S U M M a R Y A N D Conclusionmentioning
confidence: 67%
“…The Phalaborwa vermiculite also has Fe in octahedral sites. Slade and Raupach (1982) reported that the intercalation of vermiculite by benzidinium ions at pH 1.6 produces a well-ordered intercalate having a basal spacing of 19.25 ~. More recently unpublished work by one of us (P.G.S.)…”
Section: Introductionmentioning
confidence: 96%